2018
DOI: 10.1007/s11666-017-0684-9
|View full text |Cite
|
Sign up to set email alerts
|

KCl-Induced High-Temperature Corrosion Behavior of HVAF-Sprayed Ni-Based Coatings in Ambient Air

Abstract: KCl-induced high-temperature corrosion behavior of four HVAF-sprayed Ni-based coatings (Ni21Cr, Ni5Al, Ni21Cr7Al1Y and Ni21Cr9Mo) under KCl deposit has been investigated in ambient air at 600°C up to 168 h. The coatings were deposited onto 16Mo3 steel-a widely used boiler tube material. Uncoated substrate, 304L and Sanicro 25 were used as reference materials in the test environment. SEM/EDS and XRD techniques were utilized to characterize the as-sprayed and exposed samples. The results showed that the small ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Both Ni20Cr coating sprayed by HVOF and Ni21Cr coating sprayed by HVAF have shown good corrosion resistance in different environments at 600 • C for 168 h, and the thickness of the corresponding corrosion product is relatively small between 1 and 22 µm. In ambient air, Ni21Cr coating sprayed by HVAF shows similar corrosion properties as Ni5Al and NiCrAlY coatings [62], while it has performed poorly in mixed atmospheres [58]. NiCrAlY material has high oxidation resistance, and its thermal expansion coefficient is close to that of the base Fe alloy materials [40], which is widely used in coating materials.…”
Section: Ni-based Coatingsmentioning
confidence: 98%
See 1 more Smart Citation
“…Both Ni20Cr coating sprayed by HVOF and Ni21Cr coating sprayed by HVAF have shown good corrosion resistance in different environments at 600 • C for 168 h, and the thickness of the corresponding corrosion product is relatively small between 1 and 22 µm. In ambient air, Ni21Cr coating sprayed by HVAF shows similar corrosion properties as Ni5Al and NiCrAlY coatings [62], while it has performed poorly in mixed atmospheres [58]. NiCrAlY material has high oxidation resistance, and its thermal expansion coefficient is close to that of the base Fe alloy materials [40], which is widely used in coating materials.…”
Section: Ni-based Coatingsmentioning
confidence: 98%
“…Under the simulated biomass boiler atmosphere of 550 • C, HVOF-sprayed Ni5Al coating has exhibited poor corrosion resistance and failed for 672 h [60]. However, under an air or simulated atmosphere of 600 • C, the Ni5Al coating has relatively low corrosion weight changes and corrosion product layer thickness [58,61,62]. With the increase in aluminum content, the corrosion resistance of NiAl(Ni31Al) coating has been improved under the condition in which the temperature is higher than 600 • C [24,49].…”
Section: Ni-based Coatingsmentioning
confidence: 99%
“…Specifically, nearly fully dense Ni-based coatings with the ability to form different protective scales (alumina, chromia, and alumina-chromia) have been studied in considerable detail and also subjected to both laboratory and field testing. The corrosion performance of candidate HVAF-sprayed coatings-Ni 21 Cr, Ni 21 Cr 7 AlY, Ni 5 Al, Ni 21 Cr 9 Mo, Ni 21 Cr 9 Mo-SiO 2 -has been evaluated through detailed laboratory studies in ambient air, moisture, and HCl-laden environments [36][37][38][39][40][41]. All coatings were highly protective in all environments in the absence of KCl due to the formation of corresponding protective scales of alumina or chromia on the coating surface.…”
Section: Corrosion Protection Coatingsmentioning
confidence: 99%
“…The performance of the coatings in the complex Cl-containing environment was ranked as (from highest to lowest corrosion resistance): Ni21Cr9Mo-SiO2 > Ni21Cr7AlY > Ni5Al > Ni21Cr9Mo > Ni21Cr, confirming the enhanced corrosion protection of chromia-forming coatings in the presence of alloying elements and dispersed SiO2. While a typical result is summarized in Figure 4, further details regarding this work are available in the various publications mentioned previously [36][37][38][39][40][41].…”
Section: Corrosion Protection Coatingsmentioning
confidence: 99%
“…The corrosion behaviour of HVAF-sprayed NiCr, NiAl and NiCrAlY coatings has recently been investigated when exposed to ambient air at 600 °C with KCl present for 168 h [24]. It was shown that all three coatings managed to protect the substrate from corrosion attack during the time interval of the exposure.…”
Section: Oxidation In Water Vapour In the Presence Of Kclmentioning
confidence: 99%